Towards a Discussion of the Generative Condition of the Architectural Model - Couto Duarte, João; Belo Rodeia, Teresa (Design/Arts/Culture, 2022)
This paper proposes reflection on the model’s place in the definition of the architect’s thought. The representation – and, accordingly, the model, too – is assumed as an instance where the design thought becomes comprehensible, and not just something else that can be communicated. The generative condition of the model is assumed, and decisive for this is the recognition of the radical distinction that will always exist between the model and its object. Both the apparent natural proximity between the model and the architectural objects, whereby said proximity is the result of the three-dimensionality and the building dimension that both share, and the apparent natural concordance between the model and the architect’s thought are called into question. Because the aim is to understand ‘how’ an architect thinks, and not ’what’ they think when they use a model, the reflection is executed from a perspective of a horizon of ‘anteriority’, an ‘anteriority’ that is ontological and not merely chronological. The model will be examined as a means of ordering the design thought, that is, as a way of giving it existence. This reflection results from the crossing of previous research on the model and on drawing (Anonymous, 2016; Anonymous, 2017). The paper proposes a confrontation of the ‘generative power’ of the drawing, identified by Robin Evans (1997b), with the ‘generative effect’’ of the model explored by Peter Eisenman (1981a; 1981b). The principle of ‘logical Argumentation’, as defined by Groat and Wang (2002), is assumed as the method of inquiry.